Aberrant PI3Kδ splice isoform as a potential biomarker and novel therapeutic target for endocrine cancers - Ha, Siyoung; Gujrati, Himali; Wang, Bi-Dar (Frontiers in Endocrinology, 2023)
PI3K/AKT signaling pathway is upregulated in a broad spectrum of cancers. Among the class I PI3Ks (PI3Kδ/β/δ isoforms), PI3Kδ has been implicated in hematologic cancers and solid tumors. Alternative splicing is a post-transcriptional process for acquiring proteomic diversity in eukaryotic cells. Emerging evidence has highlighted the involvement of aberrant mRNA splicing in cancer development/progression. Our previous studies revealed that PIK3CD-S is an oncogenic splice variant that promotes tumor aggressiveness and drug resistance in prostate cancer (PCa). To further evaluate the potential of utilizing PI3Kδ-S (encoded from PIK3CD-S) as a cancer biomarker and/or drug target, comprehensive analyses were performed in a series of patient samples and cell lines derived from endocrine/solid tumors. Specifically, IHC, immunofluorescence, western blot and RT-PCR assay results have demonstrated that PI3Kδ isoforms were highly expressed in endocrine/solid tumor patient specimens and cell lines. Differential PIK3CD-S/PIK3CD-L expression profiles were identified in a panel of endocrine/solid tumor cells. SiRNA knockdown of PIK3CD-L or PIK3CD-S differentially inhibits AKT/mTOR signaling in PCa, breast, colon and lung cancer cell lines. Moreover, siRNA knockdown of PTEN increased PI3Kδ levels and activated AKT/mTOR signaling, while overexpression of PTEN reduced PI3Kδ levels and inhibited AKT/mTOR signaling in cancer cells. Intriguingly, PI3Kδ-S levels remained unchanged upon either siRNA knockdown or overexpression of PTEN. Taken together, these results suggested that PTEN negatively regulates PI3Kδ-L and its downstream AKT/mTOR signaling, while PI3Kδ-S promotes AKT/mTOR signaling without regulation by PTEN. Lastly, PI3Kδ inhibitor Idelalisib and SRPK1/2 inhibitor SRPIN340 were employed to assess their efficacies on inhibiting the PI3Kδexpressing endocrine/solid tumors. Our results have shown that Idelalisib effectively inhibited*